Towards the Open Source Reference Architectures - Nakagawa, Elisa Yumi; Maldonado, Jose Carlos (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2011)
Software architectures have received increasing attention by playing a significant role in determining the success and quality of software systems. In particular, reference architecture is a special type of architecture that captures the essence of software systems of a specific domain, achieving therefore well-recognized understanding of that domain. In spite of this, it is not observed concern in order to widely disseminate reference architectures and, as a consequence, the knowledge encompassed by these architectures. At the same time, Open Source Software (OSS) has been largely developed and used in both academy and industry. A diversity of OSS has been made available and has contributed to the software development through dissemination of knowledge that is encompassed mainly in the source code. Specifically, its success is due to OSS licences that have adequately supported its development and evolution. Thus, applying this same idea in order to disseminate reference architectures seems to be very interesting. The main contribution of this paper is to propose Open Source Reference Architecture (OSRA) that, based on principles of OSS, aims at promoting dissemination and evolution of reference architectures, intending to contribute to a more effective software development.